Detection Method of Limb Movement in Competitive Sports Training Based on Deep Learning. (18th February 2022) - Qin, Chunlin; Huo, Shenglu
Abstract : Traditional methods have the problems of insufficient accuracy and slow speed in human posture detection. In order to solve the above problems, a limb movement detection method in competitive sports training based on deep learning is proposed. The force change parameters of sports limb movements in the process of sports are computed to achieve the detection of limb movements in competitive sports training, and the limb movement characteristics in competitive sports training are extracted using a deep learning algorithm. The experimental results show that the limb movement detection method based on deep learning in competitive sports training has significantly higher detection accuracy and faster speed.